Bilateral carotico-clinoid foramen and inter-clinoid bars - Koshy, Jinu Merlin; S, Bindhu (Recent Research in Science and Technology, 2012)
The carotico-clinoid foramen is the result of ossification either of the carotico-clinoid ligament or of a dural fold extending between the anterior and middle clinoid processes of the sphenoid bone. It is anatomically important due to its relations with the cavernous sinus and its content, sphenoid sinus and pituitary gland. In this study the presence of carotico–clinoid foramen and inter-clinoid bars has been studied on 25dry skulls. In 25 dry skulls, authors have reported one skull, in which, a bilateral: foramen clinoideo caroticum and interclinoid bars are seen as a consequence of fusion of anterior, middle and posterior clinoid processes.The existence of a bony carotico-clinoid foramen may cause compression, tightening or stretching of the internal carotid artery. Further, removing the anterior clinoid process is an important step in regional surgery; the presence of a bony carotico-clinoid foramen may have high risk. Therefore, detailed knowledge of the type of ossification between the anterior and middle clinoid processes can be necessary to increase the success of regional surgery.